Simulasi Angka Keamanan Menggunakan Metode Elemen Hingga Berdasarkan Nilai Kohesi (c) dan Sudut Geser Dalam - Putera Agung Maha Agung; Zaindra Fakhri Salim; Aida Nurfitria; Aldo Wirastana Adinegara (Indonesian Society of Applied Science, 2026)
Expansive soil is a type of soil that can expand and shrink based on the moisture content. In Cisauk Subdistrict, Tangerang City, there are many damages to building structures and/ or roads caused by the expansive soil. This research is intended to identify the expansive soil, including its physical characteristics, in determining the cohesion (c) and internal shear angle (f) values using the UU (unconsolidated undrained) triaxial test. Test results indicated that the cohesion value was around 0.33 kg/cm² or 32.94 kN/m², and an internal shear angle of 20.51°. Both datasets were used to analyze slope stability modeling in defining the safety factor (SF) using PLAXIS software in 2D during rainy and dry seasons. Each condition was evaluated by the three slope variations, such as 20°, 40°, and 60°. Modeling results show that the (SF) would be higher on flatter slopes, and on the contrary, would decrease on steeper slopes. In addition, the (SF) would be higher during the dry season than the rainy season. The soil condition would be more saturated during the rainy season.